IN THE PRESCHOOL EDUCATION ORGANIZATION COOPERATION IN THE SOCIAL AND PERSONAL DEVELOPMENT OF THE CHILD - Jumanova Fotima Uralovna; Omonova Gullola Ulugmurad’s daughter (Zeta Repository, 2023)
The article reveals the essence and features of cooperative pedagogy in the organization of preschool education and the conceptual ideas of cooperation in the social and personal development of older preschoolers. The features of cooperation of older preschoolers in the process of joint activities with peers in organizations of preschool education are highlighted.